Cytoplasmic ribosomal protein L14B is essential for fertilization in Arabidopsis. (March 2020) - Luo, An; Zhan, Huadong; Zhang, Xuecheng; Du, Hewei; Zhang, Yubo; Peng, Xiongbo
Highlights: Mutation of RPL14B lead to reduced gamete fertility and seed abortion in Arabidopsis. Small rpl14b pollens germinate normally but pollen tube competitiveness is weakened. rpl14b affect pollen tube guidance by impairing cell fate specification of synergid. Abstract: Plant cytoplasmic ribosomal proteins not only participate in protein synthesis, but also have specific roles in developmental regulation. However, the high heterogeneity of plant ribosome makes our understanding of these proteins very limited. Here we reported that RPL14B, a component of the ribosome large subunit, is critical for fertilization in Arabidopsis. RPL14B is existed in a majority of organs and tissues. No homozygous rpl14b mutant is available, indicating that RPL14B is irreplaceable for sexual reproduction. Smaller–sized rpl14b pollens could germinate normally, but pollen tube competitiveness is grievously weakened. Beside, cell fate specification is impaired in female gametophytes from heterozygous rpl14b/RPL14B ovules, resulting in defect of micropylar pollen tube attraction. However, this defect could be restored by restricted expression of RPL14B in synergid cells. Successful fertilization requires normal pollen tube growth and precise pollen tube guidance. Thus our results show a novel role of RPL14B in fertilization and shed new light on regulatory mechanism of pollen tube growth and precise pollen tube guidance.